Spontaneous large-scale autolysis in Clostridium acetobutylicum contributes to generation of more spores - Liu, Zhen; Qiao, Kai; Tian, Lei; Zhang, Quan; Liu, Zi-Yong; Li, Fu-Li (Frontiers in Microbiology, 2015)
Autolysis is a widespread phenomenon in bacteria. In batch fermentation of Clostridium acetobutylicum ATCC 824, there is a spontaneous large-scale autolysis phenomenon with significant decrease of cell density immediately after exponential phase. To unravel the role of autolysis, an autolysin-coding gene, CA_C0554, was disrupted by using ClosTron system to obtain the mutant C. acetobutylicum lyc::int(72). The lower final cell density and faster cell density decrease rate of C. acetobutylicum ATCC 824 than those of C. acetobutylicum lyc::int(72) indicates that CA_C0554 was an important but not the sole autolysin-coding gene responding for the large-scale autolysis. Similar glucose utilization and solvents production but obvious lower cell density of C. acetobutylicum ATCC 824 comparing to C. acetobutylicum lyc::int(72) suggests that lysed C. acetobutylicum ATCC 824 cells were metabolic inactive. On the contrary, the spore density of C. acetobutylicum ATCC 824 is 26.1% higher than that of C. acetobutylicum lyc::int(72) in the final culture broth of batch fermentation. We speculated that spontaneous autolysis of metabolic-inactive cells provided nutrients for the sporulating cells. The present study suggests that one important biological role of spontaneous large-scale autolysis in C. acetobutylicum ATCC 824 batch fermentation is contributing to generation of more spores during sporulation.